2013
DOI: 10.1073/pnas.1319470110
|View full text |Cite
|
Sign up to set email alerts
|

Gnotobiotic mouse model of phage–bacterial host dynamics in the human gut

Abstract: Bacterial viruses (phages) are the most abundant biological group on Earth and are more genetically diverse than their bacterial prey/ hosts. To characterize their role as agents shaping gut microbial community structure, adult germ-free mice were colonized with a consortium of 15 sequenced human bacterial symbionts, 13 of which harbored one or more predicted prophages. One member, Bacteroides cellulosilyticus WH2, was represented by a library of isogenic transposon mutants that covered 90% of its genes. Once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
279
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(291 citation statements)
references
References 27 publications
8
279
0
4
Order By: Relevance
“…We acknowledge the fact that miBC is not an exhaustive collection; important bacterial taxa are still missing (for example, segmented filamentous bacteria or species of the phyla TM7 and Deferribacteres) and other microorganisms such as fungi and archaea, as well as viruses, are also important to investigate 39,40 . Moreover, key metabolic functions such as the conversion of bile acids require more detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the fact that miBC is not an exhaustive collection; important bacterial taxa are still missing (for example, segmented filamentous bacteria or species of the phyla TM7 and Deferribacteres) and other microorganisms such as fungi and archaea, as well as viruses, are also important to investigate 39,40 . Moreover, key metabolic functions such as the conversion of bile acids require more detailed investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics that arise from a lytic-lysogenic balance in the gut are still unknown. However, the active gut bacteriophages have been shown to influence bacterial population dynamics in a murine gut microbial ecosystem model (20), and to confer advantages to certain microbiome members during stress, such as antibiotic exposure (21). We presume that the active phageome of healthy people plays a critical role in maintaining the structure and function of a healthy gut ecosystem.…”
Section: Discussionmentioning
confidence: 96%
“…On one hand, there is evidence of more phageome similarity among relatives and household members compared with unrelated individuals (7,8). On the other hand, there is evidence that some phages are common to unrelated people (13,19,20,22). Stern et al (19) identified 991 bacteriophage sequences from cellular metagenomes that were shared across 124 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving deliberate introduction of purified human fecal VLP preparations into gnotobiotic mice colonized with a defined consortium of sequenced members of the human gut microbiota have shown that viral-bacterial dynamics in vivo are complex; the correlations between phage and bacterial strain abundances are not always obvious and involve negative correlations shifted in time as a result of a predator-prey dynamic, whereas prophages have linear positive correlations (35). As a consequence, answering this question promises to be challenging.…”
Section: Discussionmentioning
confidence: 99%